(3QSGdI aj GdfSH GdSJ GdJi Hjf GdMeO hGdTcQs - (3eMeO GdSYjO Hf eMjj GdOjf GdMSfj GdLRGFQj,J (B1278 (3g` s ((3YHO GdbGOQ Hf eMeO Hf jYbhH s)
(3ChdgG (B:s
(3GdMeO ddg hHYO aEfc SCdJ Yf GdfSH GdSJ GdJi Hjf GdMeO hGdTcQ , aGYde Cf GdMeO dZI gh GdKfGA HGddSGf s
(3BNQgG (B:s
(3hEKfGf ddYehe hGdNUhU ef hLg Ohf hLg , hhGMOI ddJQGOa hGdeSGhGI , LRi Gddg YfgG CFeJfG NjQkG hcJH YGe (B1278 s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
(3HjQhJ , LeYjI GdebGUO GdESdGejI (B- (3eYgO GdOQGSGJ GdESdGejI (B((3dZI (B15/26) s
Keywords: (3GddZIs